2014
DOI: 10.1002/2014ja020329
|View full text |Cite
|
Sign up to set email alerts
|

Waveforms of Langmuir turbulence in inhomogeneous solar wind plasmas

Abstract: Modulated Langmuir waveforms have been observed by several spacecraft in various regions of the heliosphere, such as the solar wind, the electron foreshock, the magnetotail, or the auroral ionosphere. Many observations revealed the bursty nature of these waves, which appear to be highly modulated, localized, and clumped into spikes with peak amplitudes typically 3 orders of magnitude above the mean. The paper presents Langmuir waveforms calculated using a Hamiltonian model describing self-consistently the reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 62 publications
5
31
0
Order By: Relevance
“…[ Krafft et al , ]. Recently, the dynamical model was used to study the resonant interaction of an electron beam with Langmuir wave packets in plasmas with random density fluctuations, under conditions typical of solar type III bursts regions [ Volokitin et al , ; Krafft et al , , ]. Comparison of the waveforms of the Langmuir waves obtained with recent measurements by the STEREO and Wind satellites showed that their characteristic features are very similar [ Krafft et al , ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ Krafft et al , ]. Recently, the dynamical model was used to study the resonant interaction of an electron beam with Langmuir wave packets in plasmas with random density fluctuations, under conditions typical of solar type III bursts regions [ Volokitin et al , ; Krafft et al , , ]. Comparison of the waveforms of the Langmuir waves obtained with recent measurements by the STEREO and Wind satellites showed that their characteristic features are very similar [ Krafft et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the dynamical model was used to study the resonant interaction of an electron beam with Langmuir wave packets in plasmas with random density fluctuations, under conditions typical of solar type III bursts regions [ Volokitin et al , ; Krafft et al , , ]. Comparison of the waveforms of the Langmuir waves obtained with recent measurements by the STEREO and Wind satellites showed that their characteristic features are very similar [ Krafft et al , ]. Moreover, the model was used to study the statistics of Langmuir waves when the decay instability is developed as well as particle acceleration and diffusion processes at work in the fluctuating plasma [ Krafft and Volokitin , ; Volokitin and Krafft , ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers (Krafft et al 2015a(Krafft et al , 2015bKrafft & Volokitin 2016), the authors discussed the influence of the random density inhomogeneities of the background solar wind plasma on the Langmuir decay processes. In particular, it was shown thatif several aspects of the weak turbulence theory in uniform plasmas could be used to describe the phenomena (as, for example, the values of the wavenumbers of the product waves), some important differences were evidenced compared to the case of homogeneous or quasi-homogeneous plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…These complicated spectra often have the form of the superposition of two or more spectral peaks. It is believed that these spectra result from the Doppler shift of back‐scattered waves, plasma density inhomogeneities [ Smith and Sime , ; Krasnoselskikh et al , ; Krafft et al , ; Voshchepynets et al , ], or nonlinear three‐wave interactions of two Langmuir waves with ion acoustic or transverse electromagnetic waves [ Robinson , ; Bale et al , ; Soucek et al , ; Graham and Cairns , , , and reference therein]. The presence of Langmuir waves has been reported in the upstream region of all planets from Venus to Neptune observed by a number of spacecraft including Voyager 1 and 2 [ Gurnett et al , ; Scarf et al , ; Gurnett et al , , ], Galileo [ Hospodarsky et al , ], Cassini [ Hospodarsky et al , ; Píša et al , ], Cluster [ Soucek et al , ; Sigsbee et al , ], Wind [ Bale et al , ], and STEREO [ Malaspina et al , ].…”
Section: Introductionmentioning
confidence: 99%